I didn't know what you ment but still ill try my best:
Answer: x,11
Step-by-step explanation:
Simplifying
-47 = 2x + 2x + -3
Reorder the terms:
-47 = -3 + 2x + 2x
Combine like terms: 2x + 2x = 4x
-47 = -3 + 4x
Solving
-47 = -3 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
-47 + -4x = -3 + 4x + -4x
Combine like terms: 4x + -4x = 0
-47 + -4x = -3 + 0
-47 + -4x = -3
Add '47' to each side of the equation.
-47 + 47 + -4x = -3 + 47
Combine like terms: -47 + 47 = 0
0 + -4x = -3 + 47
-4x = -3 + 47
Combine like terms: -3 + 47 = 44
-4x = 44
Divide each side by '-4'.
x = -11
Simplifying
x = -11